Year book of agricultural co-operation 1977 - Webster, F.H.; The Plunkett Foundation for co-operative studies; The International Co-operative Alliance (Cambridge : W. Heffer & Sons Ltd., 1977)
This book compiled all the activities of small and medium enterprises, including the private business cooperation's in 1977
Includes index.
Includes bibliographical references: p. 281-326.
asm 23/01/2019
Ref
Keywords: Agriculture, Cooperative